Rock cavern as thermal energy storage - Berglund, Simon (Luleå tekniska universitet, Energivetenskap, 2020)
In the fall of 2019, a comprehensive idea study was conducted on heat storage in two rock caverns located at Näsudden in Skelleftehamn and was part of the project course "Energiteknik, huvudkurs" at Luleå University of Technology. This idea study investigated the conditions of using waste heat from Boliden AB:s copper smeltery (Rönnskär) and storing this waste heat in two rock caverns and use them as seasonal thermal storage tanks, with the purpose of using the heat in the nearby district heating network, thus replacing some of the oil burned at Rönnskär. To investigate this, the authors of the idea study looked at two different storage cycles of seasonal storage and modeled this in ANSYS Fluent to simulate the heat storage and the heat losses. The results from this idea study showed promising results for using these caverns as heat storage and this work is therefore a continuation of the idea study. Since the study provided a good understanding of the conditions for seasonal storage, some questions arose about how the rock caverns will behave during an intermittent operation, which is the planned mode of operating the caverns in case of deployment. In this thesis, intermittent operation of these caverns are explored and how this effects the temperature in the caverns and its surrondings, the charge/discharge speed, how insulated walls affect the operation and how much oil is replaced. At the beginning of this project a review of the idea study and similar projects was done to gain deeper knowledge about the subject, but also to get a wider grasp on the different problems that could arise during the thesis. Relevant data for the caverns was collected and acquired to get a deeper understanding of its geometry, layout and what kind of modifications are really possible. Further data from the district heating networks of Boliden AB and Skellefteå Kraft was acquired. The available waste heat from Rönnskär was examined and used to calculate the chargeable energy by hour for the caverns, with the limits of ...